2023
DOI: 10.1123/mc.2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

External Focus Reduces Accuracy and Increases Antagonist Muscle Activation in Novice Adolescent Soccer Players

Abstract: Instep kick is one of the most effective kicking techniques in soccer. Lower extremity muscles and joints play a crucial role during instep kick. However, external (EF) and internal focus and their effect on the muscles are still ambiguous. In this study, 13 male adolescent soccer players were included and aimed to hit the targets in internal and EF conditions. Lower extremity muscle activations were measured with surface electromyography, and kinematics were measured with a high-speed video camera. Muscle act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Interestingly, while external focus has been demonstrated to improve performance in adult athletes, there may be evidence that an external center of foci may counterintuitively worsen athletic performance in adolescent athletes. Investigators found that novice adolescent athletes showed a worsened performance, as measured using muscle activation and movement latency, when attempting to kick a soccer ball at a given target [30]. The authors go on to hypothesize that younger, more novice athletes are not yet proficient in their sport-specific motor control.…”
Section: Alternative Factors Contributing To Injury In Youth Athletesmentioning
confidence: 99%
“…Interestingly, while external focus has been demonstrated to improve performance in adult athletes, there may be evidence that an external center of foci may counterintuitively worsen athletic performance in adolescent athletes. Investigators found that novice adolescent athletes showed a worsened performance, as measured using muscle activation and movement latency, when attempting to kick a soccer ball at a given target [30]. The authors go on to hypothesize that younger, more novice athletes are not yet proficient in their sport-specific motor control.…”
Section: Alternative Factors Contributing To Injury In Youth Athletesmentioning
confidence: 99%